Evidence Limitations in Determining Sexually Dimorphic Outcomes in Pediatric Post-Traumatic Hypopituitarism and the Path Forward - West, Alina Nico; Diaz-Thomas, Alicia M.; Shafi, Nadeem I. (Frontiers in Neurology, 2020)
Neuroendocrine dysfunction can occur as a consequence of traumatic brain injury (TBI), and disruptions to the hypothalamic-pituitary axis can be especially consequential to children. The purpose of our review is to summarize current literature relevant to studying sex differences in pediatric post-traumatic hypopituitarism (PTHP). Our understanding of incidence, time course, and impact is constrained by studies which are primarily small, are disadvantaged by significant methodological challenges, and have investigated limited temporal windows. Because hormonal changes underpin the basis of growth and development, the timing of injury and PTHP testing with respect to pubertal stage gains particular importance. Reciprocal relationships among neuroendocrine function, TBI, adverse childhood events, and physiological, psychological and cognitive sequelae are underconsidered influencers of sexually dimorphic outcomes. In light of the tremendous heterogeneity in this body of literature, we conclude with the common path upon which we must collectively arrive in order to make progress in understanding PTHP.